CHILD LINEAGE DETERMINATION IN UNDERAGE MARRIAGES: A PROGRESSIVE JUDICIAL PERSPECTIVE - Syafruddin, Rezki Amaliah; Basri, Rusdaya; L, Sudirman; Said, Zainal; Muchsin, Agus (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
This research examines the legal and sociological dynamics in the determination of a child's lineage within the framework of Indonesian law, particularly focusing on cases that deviate from established regulations. Specifically, the study analyzes Decision No. 90/Pdt.P/2023/PA.Pare, where a child born from an unregistered marriage was declared legitimate despite the non-fulfillment of age requirements by one of the parents. The research employs a normative juridical approach through library research, utilizing document studies to gather relevant legal and sociological data. This method facilitates a comprehensive analysis of the legal reasoning applied in the case, with a focus on how the judge arrived at the decision to grant the petition for child legitimacy. The findings indicate that the judge's legal discovery method in this case was conducted on a case-by-case basis, taking into account both juridical and sociological factors. The decision reflects a progressive legal approach, where the judge prioritized the broader implications of justice and social welfare over strict adherence to legal formalities. This study contributes to the understanding of how progressive legal thought can influence judicial decisions in cases involving deviations from standard legal provisions. It offers a unique analysis of how judges may interpret the law flexibly to achieve just outcomes in complex family law cases. The research highlights the potential for progressive legal reasoning to shape future judicial practices in Indonesia, particularly in cases involving the legitimacy of children born from unregistered marriages. It suggests that such approaches could lead to more equitable outcomes in family law, aligning legal decisions with contemporary social realities.